Correlation of Family Role in Stunting Incidents in Toddlers in Sumberbendo Village, Pare District Kediri Regency - Safira, Zalza Lailatus; Wijayanti, Lumastari Ajeng; Marianthi, Dewi (Journal Keperawatan, 2025)
Background:  Stunting is a growth disorder in children caused by chronic malnutrition, so that children have a height shorter than the standard for their age. The impact of stunting is on children's growth and development, both cognitively and physically. Fulfillment of nutritional intake in toddlers is fully managed by the family, therefore the family has an important role in caring for and nurturing toddlers during the child's growth and development. Purpose: To analyze the relationship between family roles and stunting incidence. Methods: This study uses an observational analytical research design with a cross-sectional approach, the study population is parents and toddlers as many as 182 respondents with a sample size of 125 respondents taken using a simple random sampling technique. The research instrument uses Microtoice to measure the height of toddlers and a family role questionnaire. Results: Based on the results of statistical tests using chi square, the results obtained were a p value of 0.013 (p <0.05), which shows that there is a relationship between family roles and the incidence of stunting in toddlers. Conclusion: There is a significant difference in the level of difficulty of social relations between students based on the level of the diploma program in nursing at Poltekkes Kemenkes Aceh, which shows that the level of education is related to students' social adaptation abilities.